The best is yet to come - Macomber, Debbie (New York : Random House Large Print, 2022)
After the death of her twin brother, teacher Hope Godwin moves to Oceanside, Washington, where she falls in love with animal shelter volunteer, and wounded ex-marine, Cade Lincoln, Jr, . and a dog named Shadow, finally finding peace in her new home until Cade's past comes back with a vengeance.
Keywords: Twins -- Fiction; High school teachers -- Fiction; Women teachers -- Fiction; Veterans -- Fiction; Animal shelters -- Fiction; Man-woman relationships -- Fiction; Large type books; Washington (State) -- Fiction; Romance fiction